Peroxidase extraction from jicama skin peels for phenol removal - Chiong, T; Lau, S.Y; Khor, E H; Danquah, M K (2015)
Phenol and its derivatives exist in various types of industrial effluents, and are known to be harmful to aquatic lives even at low concentrations. Conventional treatment technologies for phenol removal are challenged with long retention time, high energy consumption and process cost. Enzymatic treatment has emerged as an alternative technology for phenol removal from wastewater. These enzymes interact with aromatic compounds including phenols in the presence of hydrogen peroxide, forming free radicals which polymerize spontaneously to produce insoluble phenolic polymers. This work aims to extract peroxidase from agricultural wastes materials and establish its application for phenol removal. Peroxidase was extracted from jicama skin peels under varying extraction conditions of pH, sample-to-buffer ratio (w/v %) and temperature. Experimental results showed that extraction process conducted at pH 10, 40% w/v and 25oC demonstrated a peroxidase activity of 0.79 U/mL. Elevated temperatures slightly enhanced the peroxidase activities. Jicama peroxidase extracted at optimum extraction conditions demonstrated a phenol removal efficiency of 87.5% at pH 7. Phenol removal efficiency was ∼ 97% in the range of 30 - 40oC, and H2O2 dosage has to be kept below 100 mM for maximum removal under phenol concentration tested.